Pengaruh Gaya Kepemimpinan, Motivasi Dan Komunikasi Organisasi Terhadap Komitmen Anggota Himaprodi Manajemen - Firmansyah, Alfian Dimas; Nurhidayah, Nurhidayah; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to analyze and describe the influence of leadership style, motivation and organizational communication on the commitment of management study program members. This study involved a population consisting of members of the management study program. The sample was determined using the Slovin formula, resulting in 86 respondents. Data analysis was carried out using the Structural Equation Modeling (SEM) technique with the assistance of SPSS version 30 software. The variables in this study include Member Commitment as the dependent variable, and Leadership Style, Motivation, and Communication as the independent variables. The results of the study indicate that: 1) Leadership Style does not have a significant effect on Member Commitment, 2) Motivation does not significantly influence Member Commitment, and 3) Communication has a significant influence on Member Commitment. Keywords: Member Commitment, Leadership Style, Motivation, Organizational Communication